Cimifugin Suppresses NF-κB Signaling to Prevent Osteoclastogenesis and Periprosthetic Osteolysis - Duan, Juan; Hu, Xuantao; Li, Tao; Wu, Gen; Dou, Pengcheng; Ouyang, Zhengxiao (Frontiers in Pharmacology, 2021)
Background: Aseptic loosening of prosthesis (ALP) is one of the most common long-term complications of knee and hip arthroplasty. Wear particle-induced osteoclastogenesis and subsequent periprosthetic osteolysis account for the morbidity of ALP. Here, we investigate the potential of cimifugin (CIM), a natural extract from Cimicifuga racemosa and Saposhnikovia divaricata, as a bone-protective drug in the treatment of ALP. Method: First, we performed cell viability and osteoclast formation assays to assess the effect of noncytotoxic CIM on osteoclast differentiation in vitro. Bone slice resorption and F-actin ring immunofluorescence assays were adopted to assess the effects of CIM on bone-resorption function. Then, quantitative real-time polymerase chain reaction (qRT–PCR) analysis was performed to further assess the repressive effects of CIM on osteoclastogenesis at the gene expression level. To elucidate the mechanisms underlying the above findings, Western blot and luciferase reporter gene assays were used to assess the regulatory effects of CIM on the NF-κB and MAPK signaling pathways. Moreover, a Ti particle-induced murine calvarial osteolysis model and subsequent histomorphometric analysis via micro-CT and immunohistochemical staining were used to elucidate the effect of CIM on periprosthetic osteolysis in vivo. Result: CIM dose-dependently inhibited both bone marrow-derived macrophage (BMM)- and RAW264.7 cell-derived osteoclastogenesis and bone resorption pit formation in vitro, which was further supported by the reduced expression of F-actin and osteoclast-specific genes. According to the Western blot analysis, inhibition of IB phosphorylation in the NF-κB signaling pathway, not the phosphorylation of MAPKs, was responsible for the suppressive effect of CIM on osteoclastogenesis. Animal experiments demonstrated that CIM alleviated Ti particle-induced bone erosion and osteoclast accumulation in murine calvaria. Conclusion: The current study suggested for the first time that CIM can inhibit RANKL-induced osetoclastogenesis by suppressing the NF-κB signaling pathway in vitro and prevent periprosthetic osteolysis in vivo. These findings suggest the potential of CIM as a therapeutic in ALP.